(untitled) (Research, Society and Development, 2021)
Nitrogen compounds (nitrite, nitrate and ammonia) are considered toxic to fish, as they can promote histological and biochemical changes, decrease the oxygen-carrying capacity in the blood and affect fitness (ie the body’s fitness in terms of growth and swimming). These compounds accumulate in the aquatic environment through the excretion of aquatic organisms, decomposition of organic matter from both aquatic and adjacent terrestrial systems, and direct entry into the terrestrial system, tributaries and groundwater. The so-called global changes, such as climate and land-use changes, can enhance and intensify this entry of nitrogen compounds through human activities, such as agriculture and the release of effluents, such as domestic sewage. Fish are commonly in contact with various pollutants, and the combination of environmental factors such as temperature, pH, oxygen availability and hardness can have synergistic or antagonistic effects. However, how these environmental factors affect the toxicity of ammonia, nitrite and nitrate are not fully understood. Therefore, our objective was to review the literature to address the effects of nitrogen compounds, and how the physicochemical parameters of water affect the toxicity of these compounds.